Peningkatan Kualitas Pendidikan Oleh Mahasiswa KKN di Desa Domas Kecamatan Trowulan Kabupaten Mojokerto - Riska Ayu Rahmaida; Alifatur Mustofa; Sjarief Hidajat (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Education is a crucial foundation for building quality human resources and community welfare. The Thematic Community Service Program (KKN) conducted by students of UPN "Veteran" East Java in Domas Village aimed to improve the quality of education in the village. The method used was direct participation in teaching and learning activities and socialization. The main activities included interactive teaching at MI Al-Hidayah, additional tutoring "Sinau Bareng" at the village hall, creative competitions, and socialization on bullying prevention. The results of these activities showed an increase in students' interest and enthusiasm for learning, positive support from teachers and parents, and increased awareness about bullying among students. These activities demonstrate that interactive and participatory approaches can bring significant positive changes in the quality of education.